Model For Microeconomic Empowerment: Islamic Microfinance Institutions (Imis) In East Java - HERIANINGRUM, S.; SHOFAWATI, A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT East Java is one of the provinces in Indonesia in which the government has strongly supported the development of Islamic economics. The implementation of Islamic economics is expected to contribute to the economic development of East Java. Therefore, this research examines the economic empowerment of micro-enterprises conducted by Islamics Microfinance Institutions. Qualitative research methods were used, with particular reference to case studies. The results showed that Islamics Microfinance Institutions financing channeled towards microenterprises was capable of empowering them. RESUMEN Java Oriental es una de las provincias de Indonesia en las que el gobierno ha apoyado firmemente el desarrollo de la economía islámica. Se espera que la implementación de la economía islámica contribuya al desarrollo económico de Java Oriental. Por lo tanto, esta investigación examina el empoderamiento económico de las microempresas realizadas por las instituciones islámicas de microfinanzas. Se utilizaron métodos de investigación cualitativa, con referencia particular a estudios de casos. Los resultados mostraron que el financiamiento de las Instituciones Islámicas de Microfinanzas canalizadas hacia las microempresas fue capaz de empoderarlas.